Assessing brain computed topography findings of HIV infected adults presenting with primary headaches in Johannesburg, South Africa - Gengan, Kerena (My University, 2019)
Introduction: Despite the high prevalence of Human Immunodeficiency Virus (HIV) infected individuals in South Africa, there are currently no studies which investigate primary headaches in this population. The primary aim of this study was to describe the computed tomography (CT) brain findings of HIVinfected individuals with primary headache. The study also aimed to evaluate any associations between demographic factors, HIV-related factors and CT brain findings. Methods: This was a prospective study. Adult HIV-infected individuals who met the International Classification of Headache Disorders (ICHD)3 beta criteria for primary headache disorders were included in the study. Demographic information, HIV-related information and headache characteristics were collected. All participants had CT brain scans performed. Fischers’ exact test was used to test for any significant associations between demographic factors, HIV-related factors and CT findings. A P-value < 0.05 was considered significant. Results: Eighty-six participants were included in the study. Ten (12%) participants had abnormal CT brain scans. The abnormalities included calcified granulomas, cerebral atrophy, periventricular white matter ischaemic changes and an arachnoid cyst. There were no statistically significant associations found between CT findings and age, sex, headache type, headache severity, viral suppression, CD4 count and presence or absence of antiretrovirals (ARVS). There was a statistically significant association between co-morbidities and CT findings (30% vs. 83%; p= 0.001). Conclusion: In HIV-infected individuals with ICHD3 beta defined primary headache, there is a low prevalence of abnormalities on CT brain scans. HIV-infected individuals with co-morbidities are more likely to have abnormal CT brain scans. HIV, by itself, is not associated with abnormal CT brain scans in individuals with primary headaches.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment for the degree of Master of Medicine in the division of Neurology, Johannesburg 2019
Keywords: Brain--radiography; Tomography-X-Ray computed; Radiology